Federal prisons (Revista do Tribunal Regional Federal da 3ª Região, 2010)
The text speaks about federal prisons in the Brazil. To discourse about of the destination, conformity, structure and functioning federals prisons. Make reference about the cost of the system and the perspective resocialization of the prisoner. Approach the process and procedure of the inclusion of prisoner in the federal penitentiary system and aspects of the execution of the punishment. To broach a subject the principles of prohibition of the excess and the prohibition of the deficient protection.
Keywords: federals prisons; structure; functioning; cost of the system; ressocialization; process and procedure; execution of the punishment